Extraordinary, ordinary people [compact disc, unabridged] : a memoir of family - Rice, Condoleezza, 1954- (Random House, Inc., 2010)
Condoleezza Rice, the former U.S. Secretary of State and National Security Advisor, presents a stunning memoir that goes deeper than just her political career. Here, Rice unveils the story of a young woman coming into her own in a turbulent, ever-changing world and examines how her parents and tight-knit community helped her rise above the violent and extreme racism of her hometown of Birmingham, Alabama, succeed at the prestigious Stanford University, and go toe-to-toe with world leaders.